2015
DOI: 10.17305/bjbms.2015.503
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotrophin-1: A new predictor of atrial fibrillation relapses after successful cardioversion

Abstract: We aimed to investigate whether or not cardiotrophin-1 (CT-1) can be used as a predictor of sinus rhythm constancy in patients with atrial fibrillation (AF) converted to sinus rhythm. Thirty two patients with AF (48-78 years), without any structural heart disease were enrolled for the study. The control group consisted of 32, age and gender matched healthy persons. Measurements of CT-1 were made after transthoracic and transesophageal echocardiography prior to cardioversion (CV). Relapses of AF were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
8
1
Order By: Relevance
“…In our study, especially in patients with STEMI, CT-1 levels increased more than the other ACS groups, supporting its myocardial protective effects in terms of prognosis. Altun et al found a positive correlation between CT-1 levels and recurrence of AF after cardioversion in 32 patients with AF (19). In our study, AF was detected in 4 patients; but CT-1 levels were not different between groups with and without AF.…”
Section: Discussioncontrasting
confidence: 57%
“…In our study, especially in patients with STEMI, CT-1 levels increased more than the other ACS groups, supporting its myocardial protective effects in terms of prognosis. Altun et al found a positive correlation between CT-1 levels and recurrence of AF after cardioversion in 32 patients with AF (19). In our study, AF was detected in 4 patients; but CT-1 levels were not different between groups with and without AF.…”
Section: Discussioncontrasting
confidence: 57%
“…This is the first study to report that increased EFT thickness is associated with cardioversion failure. The number of novel indices including recurrent AF‐related echocardiographic parameters, such as left atrium volume index, atrial emptying fraction, and biomarkers such as cardiotroponin‐1 and NT ProBNP are increasingly used . These predictors may be valuable when making decisions about rhythm control in clinical practice and during ECV planning.…”
Section: Discussionmentioning
confidence: 99%
“…The receiver operating characteristic (ROC) curve analysis of platelet-to-lymphocyte ratio for predicting atrial fibrillation recurrence and different novel indices such as echocardiographically determined left atrial volume index and atrial emptying fraction, and biomarkers including cardiotroponin-1 and N-terminal pro-brain natriuretic peptide (NT-proBNP) are increasing (Altun et al, 2015;Andersson, Rosenqvist, Tornvall, & Boman, 2015;Luong et al, 2016;Toufan, Kazemi, & Molazadeh, 2017). These predictors may serve as a valuable tool when determining the rhythm control in clinical practice and when planning ECV; however, less expensive and more practical measures are required to predict recurrences.…”
Section: Discussionmentioning
confidence: 99%